Case Report: Clinical and genetic analysis of a family with hereditary spherocytosis combined with familial chylomicronemia syndrome - Qin, Yumei; Liu, Yanping; Li, Kecheng; Deng, Yaoming; Li, Hualian; Chen, Xiao; Pan, Xuan; Huang, Xiaojing; Xie, Mengyue; Long, Xingjiang; Tang, Shifu (Frontiers in Genetics, 2026)
ObjectiveThis study was conducted to investigate the clinical and genetic characteristics of a family affected by hereditary spherocytosis (HS) combined with familial chylomicronemia syndrome (FCS), identify the pathogenic cause, and provide a basis for the clinical diagnosis, treatment, and genetic counseling of affected children.MethodsClinical data were collected from family members. High-throughput sequencing was performed to identify pathogenic variants in genes associated with HS and FCS in the proband. Suspected pathogenic mutations were confirmed in family members via PCR-Sanger sequencing. Bioinformatics analysis and three-dimensional protein structure prediction were also conducted.ResultsThe proband presented with severe anemia, splenomegaly, and jaundice. Genetic testing revealed a heterozygous mutation, c.6005G>A (p.Trp2002*), in the spectrin beta chain (SPTB)gene (NM_001355436.2) and a missense mutation, c.292G>A (p.Ala98Thr), in the lipoprotein lipase (LPL) gene (NM_000237.3). The SPTB c.6005G>A (p.Trp2002*) mutation was inherited from the mother, who exhibited mild anemia, jaundice, and splenomegaly. The LPL c.292G>A (p.Ala98Thr) mutation was inherited from the father, who had hypertriglyceridemia. The SPTB c.6005G>A (p.Trp2002*) mutation is extremely rare in the general population.ConclusionThe heterozygous mutations SPTB c.6005G>A (p.Trp2002*) and LPL c.292G>A (p.Ala98Thr) are the pathogenic causes in this family and provide a basis for clinical management and genetic counseling. Based on the HGMD, 1000G, and ExAC databases, the SPTB c.6005G>A (p.Trp2002*) mutation is reported here for the first time, enriching the mutation spectrum of the SPTB gene.